2019
DOI: 10.1108/wjemsd-10-2018-0090
|View full text |Cite
|
Sign up to set email alerts
|

How do Argentine SMEs define CSR? Cases in educational social development

Abstract: Purpose The purpose of this paper is to investigate the social responsibility approaches of six small and medium-sized enterprises (SMEs) in Argentina and their definitions of corporate social responsibility (CSR). Design/methodology/approach This is an exploratory, qualitative study and part of a broader study. A sample of six Argentine SMEs from manufacturing, services and construction sectors was used to evaluate specific CSR initiatives in the areas of social development. A total of 23 interviews were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Construction industry stakeholders show an understanding that it is beneficial to implement CSR initiatives for the benefit of all. Findings agree with Visser (2010), Claydon (2011), Abugre and Nyuur (2015), Massoud et al . (2019), Ebekozien et al .…”
Section: Findings and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Construction industry stakeholders show an understanding that it is beneficial to implement CSR initiatives for the benefit of all. Findings agree with Visser (2010), Claydon (2011), Abugre and Nyuur (2015), Massoud et al . (2019), Ebekozien et al .…”
Section: Findings and Discussionsupporting
confidence: 89%
“…Construction industry stakeholders show an understanding that it is beneficial to implement CSR initiatives for the benefit of all. Findings agree with Visser (2010), Claydon (2011), Abugre and Nyuur (2015), Massoud et al (2019), Ebekozien et al (2022a, b) and Aigbavboa et al (2024). Visser (2010) argued that CSR should be an integral part of the change needed for a society to enable sustainability of the planet and reverse poverty.…”
Section: Stakeholders Understanding Of Csrsupporting
confidence: 83%
See 1 more Smart Citation
“…The present study also found that the topic of education was more prevalent in sustainability reports from developing countries than from developed countries, in agreement with previous findings (Chapple and Moon, 2005;Makka and Nieuwenhuizen, 2018;Massoud et al, 2019). The developing world is facing problems that, to a large extent, could be resolved by improving education (Kvasničková Stanislavská et al, 2020), making it logical for companies in developing countries to devote special attention to education in their CSR programs.…”
Section: Regional Viewsupporting
confidence: 92%
“…Education is also recommended as the best way to raise awareness of the social and environmental role of businesses [105]. The importance of education in the context of CSR activities in developing countries has been further highlighted by Massoud, Daily and Willi [106] in Argentina. In a sample of small and medium-sized businesses, the authors identified employees, community, the natural environment and education as the key elements underlying the perception of CSR commitment.…”
Section: Discussion and Implicationmentioning
confidence: 99%